Dialectical lexis represented in Ratko Popović's collection of poems - Jašović Golub M. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2013)
This paper deals with dialectical lexics found in a poem collection named Straori written by a well-known author from Kosovo and Metohija, Ratko Popović. The book is consisted of 52 songs, mostly written in prizrensko - southmoravian dialect. Lexical materials were analyzed, classified and compared with data published in the Dictionary of Kosovo and Metohija dialects by Glisa Elezović and also in Dictionary of Ugljare near Priština by Golub Jašović. During the material extraction our main concerns were to use dialecticisms, regionalisms and localisms that are used in the same form in Serbian dialects of Gračanica natives, and also that these elements do not occur in Dictionary of Serbo-Croatian literary language published by Matica srpska. Semantics and form of chosen elements differ from those found in Popović's book and Gračanica's dialects. Lexical, semantical, and formational analysis were used in the research of house and household names, and also in cattle, crop and fruit lexics and terminology. Also, of lexics used in the naming of birds and animals, food and drinks, clothes and also for the names of board games, of faith and believes, administrative names etc. Microtoponyms and oikonyms found in Straori were classified as a special dialectical subgroup. Foreign dialectisms, mostly of Greek and Eastern origins, were also analyzed.